Studi Kelayakan Finansial dan Penentuan Komposisi Penumpang Sarana Transportasi Masal Monorail dengan Berbagai Skenario Jumlah Penumpang (Studi Kasus Jalur Monorail Kampung Melayu-Roxy) - Leli Deswindi (Universitas Bunda Mulia, 2017)
Jakarta is a city with high level of traffic problems caused by large number of vehicles. To solve this problem, the local government signed the agreement to build a mass rapid transportation (Monorail) which is assumed more comfortable, faster and cheaper. A feasibility study in term of financial analysis to determine which project should be chosen based on total number of passengers scenarios and the composition of passengers in three ticket price levels (Rp. 3500, Rp. 5500, and Rp. 7500) is described in this research. Using the NVP and the payback period methods, this research concluded that scenario 4, with total number of passengers 150000 persons/day, will provide the highest profit (Rp.890.208.651.879) at a composition number of passengers 1:1:1. This project will still be considered feasible if the total number of passengers decrease at the level of max 42%/day. The lost position is at the level 75000 passengers / day with composition of passengers 2:2:1. At a level of 75000 passengers / day, the project will profit by the increase number of passengers up to 100000/day at 3rd year, with the composition 3:2:1. Another alternative is by establishing a ticket price at Rp2500 for the first 2 years operation time and at Rp. 1000 for the next 20 years, with total number of passengers is 75000 in 1st year, 100000 in 2nd, 125000 in 3rd, 150000 at 4th and continues at this level until the 20th year. The profit will be at Rp 831.133.279.548 by that time and the payback period is 9 years and 1.7 months, predicted.Keywords: Financial Analysis, NPV, Payback Period, Monorail